Sleep disturbance in patients with cancer: a feasibility study of multimodal therapy. Issue 2 (10th January 2020) - Yennurajalingam, Sriram; Carmack, Cindy; Balachandran, Dave; Eng, Cathy; Lim, Bora; Delgado, Marvin; Guzman Gutierrez, Diana; Raznahan, Monica; Park, Minjeong; Hess, Kenneth R; Williams, Janet L; Lu, Zhanni; et al.
Abstract : Background: Our aim was to determine feasibility and effect sizes of bright light therapy (BLT), melatonin (MLT), methylphenidate (MP) and eight combinations (BLT+MLT+MP, BLT+MLT, BLT+MP, BLT alone, MLT+MP, MLT alone, MP alone, placebo for BLT, MLT and MP) defined as multimodal therapy (MMT), to improve sleep quality (SQ) (Pittsburgh Sleep Quality Index (PSQI)) from baseline to day 15. We also examined the effects of MMT on insomnia, fatigue, depression, quality of life and actigraphy. Methods: Patients with advanced cancer with poor SQ (PSQI ≥5) were eligible. Using a double-blind randomised factorial study design, patients were randomised into 1 of the 8 arms for 2 weeks. Feasibility and effect sizes were assessed. Results: 81% (54/67) of randomised patients completed the study. There were no differences in the demographics and SQ between groups. The adherence rates for BLT, MLT and MP were 93%, 100% and 100%, respectively. BLT+MLT+placebo of MP; BLT+placebo of MLT+placebo of MP; BLT+MLT+MP showed an effect size (Cohen's d) for change in PSQI scores of 0.64, 0.57 and 0.63, respectively. PSQI change using linear regression showed BLT (n=29) has effect size of 0.46, p=0.017; MLT (n=26), 0.24, p=0.20; MP (n=26), 0.06, p=0.46. No significant differences were observed in scores for insomnia, fatigue, depression, quality of life and actigraphy. There were no differences in adverse events by groups(p=0.80). Conclusions: The use of MMT to treat SQ disturbance was feasible. BLT+MLT showed the most promising effect size in improvement in SQ, and additional larger studies are needed. Trial registration number: NCT01628029 .